1999
DOI: 10.1093/nar/27.6.1555
|View full text |Cite
|
Sign up to set email alerts
|

Rapid modification of bacterial artificial chromosomes by ET- recombination

Abstract: We present a method to modify bacterial artificial chromosomes (BACs) resident in their host strain. The method is based on homologous recombination by ET-cloning. We have successfully modified BACs at two distinct loci by recombination with a PCR product containing homology arms of 50 nt. The procedure we describe here is rapid, was found to work with high efficiency and should be applicable to any BAC modification desired.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
351
0
4

Year Published

2000
2000
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 490 publications
(361 citation statements)
references
References 0 publications
5
351
0
4
Order By: Relevance
“…These experiments confirm the early obervations of others (Zhang et al, 1998;Yu et al, 2000): recombineering can be as useful a tool for modifying plasmid replicons as it is for BACs Muyrers et al, 1999), the bacterial chromosome (Yu et al, 2000;Ellis et al, 2001;Costantino and Court, 2003;Thomason et al, 2005b), and phage λ itself (Oppenheim et al 2004), but there are complexities associated with multicopy plasmids that do not arise with the other replicons. ssDNA recombineering in the absence of mismatch repair targeted to plasmids is of such high efficiency that it can be used to isolate point mutations or changes of only a few bases without selection.…”
Section: Discussionsupporting
confidence: 74%
“…These experiments confirm the early obervations of others (Zhang et al, 1998;Yu et al, 2000): recombineering can be as useful a tool for modifying plasmid replicons as it is for BACs Muyrers et al, 1999), the bacterial chromosome (Yu et al, 2000;Ellis et al, 2001;Costantino and Court, 2003;Thomason et al, 2005b), and phage λ itself (Oppenheim et al 2004), but there are complexities associated with multicopy plasmids that do not arise with the other replicons. ssDNA recombineering in the absence of mismatch repair targeted to plasmids is of such high efficiency that it can be used to isolate point mutations or changes of only a few bases without selection.…”
Section: Discussionsupporting
confidence: 74%
“…All three Bmp7 knockout alleles show very similar phenotypes in homozygosis, though some differences have been noted, particularly with respect to penetrance of the kidney al., 2003). The targeting vector was assembled on the BAC by two rounds of Bacterial Homologous Recombination (Muyrers et al, 1999) using generic modification cassettes shown in Fig. 1B.…”
Section: Resultsmentioning
confidence: 99%
“…The simplicity of the coinjection strategy allows for efficient testing of multiple BACs for enhancer and rescue activity. More detailed studies then can be conducted by using homologous recombination in BACs (41,42) to delete or alter specific sequences to observe the effect on expression patterns. The BAC coinjection technique should facilitate the studies of control elements in many different genes.…”
Section: Discussionmentioning
confidence: 99%